Racial and Socioeconomic Disparities in the Use and Outcomes of Endovascular Thrombectomy for Acute Ischemic Stroke - Mehta, A.M.; Fifi, J.T.; Shoirah, H.; Shigematsu, T.; Oxley, T.J.; Kellner, C.P.; Leacy, R.De; Mocco, J.; Majidi, S. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Racial and socioeconomic disparities in the incidence, treatment, and outcomes of acute ischemic stroke exist and have been described. We aimed to characterize disparities in the use of endovascular thrombectomy in a nationally representative analysis.MATERIALS AND METHODS: Discharge data from the Nationwide Inpatient Sample between 2006 and 2016 were queried using validated International Classification of Disease codes. Patients admitted to US hospitals with acute ischemic stroke were included and stratified on the basis of race, income, and primary payer. Trends in endovascular thrombectomy use, good outcome (discharge to home/acute rehabilitation), and poor outcome (discharge to skilled nursing facility, hospice, in-hospital mortality) were studied using univariate and multivariable analyses.RESULTS: In this analysis of 1,322,162 patients, endovascular thrombectomy use increased from 53/111,829 (0.05%) to 3054/146,650 (2.08%) between 2006 and 2016, respectively. Less increase was observed in black patients from 4/12,733 (0.03%) to 401/23,836 (1.68%) and those in the lowest income quartile from 10/819 (0.03%) to 819/44,984 (1.49%). Greater increase was observed in the highest income quartile from 18/22,138 (0.08%) to 669/27,991 (2.39%). Black race predicted less endovascular thrombectomy use (OR = 0.79; 95% CI, 0.72–0.86). The highest income group predicted endovascular thrombectomy use (OR = 1.24; 95% CI, 1.13–1.36) as did private insurance (OR = 1.30; 95% CI, 1.23–1.38). High income predicted good outcome (OR = 1.10; 95% CI. 1.06–1.14), as did private insurance (OR = 1.36; 95% CI, 1.31–1.39). Black race predicted poor outcome (OR = 1.33; 95% CI, 1.30–1.36). All results were statistically significant (P < .01).CONCLUSIONS: Despite a widespread increase in endovascular thrombectomy use, black and low-income patients may be less likely to receive endovascular thrombectomy. Future effort should attempt to better understand the causes of these disparities and develop strategies to ensure equitable access to potentially life-saving treatment.AISacute ischemic strokeECIElixhauser Comorbidity IndexEVTendovascular thrombectomyICDInternational Classification of DiseaseNISNationwide Inpatient Sample